Real‐world experience for the outcomes and costs of treating hepatitis C patients: Results from the German Hepatitis C-Registry (DHC-R) - Krüger, Kathrin; Rossol, Siegbert; Krauth, Christian; Buggisch, Peter; Mauss, Stefan; Stoehr, Albrecht; Klinker, Hartwig; Böker, Klaus; Teuber, Gerlinde; Stahmeyer, Jona (Zeitschrift für Gastroenterologie, 2022)
Background & Aims With long-term consequences like the development of liver cirrhosis and hepatocellular carcinoma, chronic hepatitis C virus (HCV) infection is associated with a significant health burden. Information on HCV treatment outcomes and costs in routine care is still rare, especially for subgroups. The aim of this study was to analyse the treatment outcomes and costs of subgroups in routine care and to compare them over time with previous analyses.Methods Data were derived from a noninterventional study including a subset of 10298 patients receiving DAAs with genotypes 1 and 3. Sociodemographic, clinical parameters and costs were collected using a web-based data recording system. The total sample was subdivided according to treatment regimen, cirrhosis status as well as present HIV infection and opioid substitution treatment (OST).Results 95% of all patients achieved SVR. Currently used DAA showed higher SVR-rates and less adverse events (AE) compared to former treatments. Concerning subgroups, cirrhotic patients, HIV-coinfected patients and OST patients showed lower but still high SVR-rates. In comparison, cirrhotic had considerably longer treatment duration and more frequent (serious) AE. Overall, average treatment costs were €48470 and costs per SVR were €51129; for currently used DAAs costs amounted to €30330 and costs per SVR to €31692. After the end of treatment, physical health is similar to the general population in all patients except cirrhotic. Mental health remains far behind in all subgroups, even for currently used DAA.Conclusions Over time, some relevant factors developed positively (SVR-rates, costs, treatment duration, adverse events, health-related quality of life (HRQoL)). Further research on HRQoL, especially on mental health, is necessary to evaluate the differences between subgroups and HRQoL over time and to identify influencing factors.
Keywords: Leber; Virushepatitis; Hepatitis C; Klinische Praxis; Registerdaten; SVR; Lebensqualität; HIV; Drogenkonsumenten; Kosten